Aqua medicines, drugs and chemicals (AMDC) used in freshwater aquaculture of South-Eastern Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2021)
A broad variety of aquaculture-related medications, drugs, and chemicals (AMDC) are extensively used in the aquaculture industry in South-Eastern Bangladesh. Fish farmers are worried about the quality of their final product, and disease outbreaks must be stopped at all costs. Farmers are sometimes one ahead of the curve when it comes to producing healthy final products by including probiotics, vitamins, and minerals into their aquaculture setups to promote early and disease-free output. However, the current study was carried out in south eastern Bangladesh, specifically in the highly dense aquaculture regions of Chandpur, Cumilla, and Feni district (17 upazilas), from November 2016 to January 2018. Questions were asked through interviews and a Focus Group Discussion (FGD) was held to gather primary data. The major target groups were aquaculture farmers, AMDC shops, pharmaceutical company employees, and hatchery owners. In this three-county area, according to the findings from the thorough research, there are a total of 33 companies that advertise 330 generics brand products via their own distributional channels. Among the available AMDC products in the study area, growth promoters were mostly abundant products among all categories while other products such as predator removal products, insecticides and ectoparasiticides, water quality and pond management, plankton producer, plankton bloom cleaner, disinfectant and disease treatment, toxic gas reducer, pH controller, oxygen supply, stress reducer, growth promoter, probiotics and antibiotics were most selling products to the farmers. The present study revealed 19 generic of antibiotics were available and prescribed by the AMDC vendors or aquaculture disease consultants (ADC) around the regions. Additionally, the research also included the dosages of AMDC and the method of administration in the aquaculture pond, which will assist both the farmers and the ADC in selecting and suggesting the appropriate medications or treatments that may be beneficial to the farmers in the long run.Asian Australas. J. Biosci. Biotechnol. 2021, 6 (2), 103-127